Is lumpen its pedigree? The lumpen as a recurring poetic resource in Joaquín Sabina of the eighties (Orkopata. Revista de Lingüística, Literatura y Arte, 2025)
The lumpen as a social phenomenon has notably influenced the songwriting of singer-songwriter Joaquín Sabina. This gave him the reputation of an artist interested in incorporating characters and scenes linked to lumpen environments into his lyrics, environments he himself frequented and participated in, mainly during the 1970s and 1980s. The lumpen, a category brought to prominence by Marx and Engels and later addressed by other theorists like Walter Benjamin, is the concept to explore in this study through Joaquín Sabina's songs. He adopted this figure as a fundamental element of his poetic songwriting because it fit well with a model that resonated with his youthful and rebellious spirit, which led him to clandestinely exile to London in the late 1970s. The lumpen has endowed many of his lyrics with a sense of romanticism and insubordination. Characters such as delinquents like El Jaro or El Dioni, or bohemians like the magician Tolito, parade through his work. Over time, this trait has gradually diminished in his albums but has never completely disappeared. The lumpen universe, therefore, has become a characteristic hallmark of Sabina, who leaves in his work a social testimony of a lived time.
Keywords: creative writing; literary style; Joaquín Sabina; lumpen; marginality